SISTEM PENDUKUNG KEPUTUSAN PEMBELIAN SMARTPHONE ANDROID DENGAN METODE MULTI ATTRIBUTE UTILITY THEORY (MAUT) - Pristiwati Fitriani (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2020)
Buying a smartphone is very coveted among the people, many models and types of smartphones of various brands confuse people to buy a smartphone that requires new knowledge to solve the problem. The method used in this research is a literature study of various smartphone prices starting from the website and local prices. The criteria used are price, memory space, Ram space and smartphone advantages. The results of this study show that smartphones are the best of various smartphones. with this the purchase of a smartphone can be done computationally using the Multi-Attribute Utility Theory (MAUT) method. MAUT method is a decision method to make the results more precise based on the attributes and criteria that are with the system utility. Furthermore, this method has features of the compensation method. attributes are independent of each other and qualitative attributes are transformed into quantitative attributes.